Heat treatment and quenching effects on wear of electroless nickel–phosphorous plating. Issue 1 (1st January 2021) - Shetty, Abhishek D..; Shivamurthy, B.; Thimmappa, B. H. S.; Parmar, Yash
Abstract: This work aims to evaluate the effect of post-heat treatment and quenching on the hardness, coating thickness, morphology, wear, and microstructure of the coatings made on steel travelers. The test result shows that all the quenched samples have similar hardness. Wear tests of the specimens show that Type-I oil quenched specimens have better wear resistance compared to other specimens. Atomic force microscope results reveal that Type-I oil-quenched travelers have a smoother surface than water and air-cooled travelers. Scanning electron microscope images show that the distribution of plating on the substrate is not uniform. After baking, the coating becomes uniform. However, some small voids are present in the coating due to improper surface activation before the plating process.